Museum Thresholds
1 online resource (xviii, 262 pages)
Keywords: "Museum Thresholds is a progressive, interdisciplinary volume and the first to explore the importance and potential of entrance spaces for visitor experience. Bringing together an international collection of writers from different disciplines, the chapters in this volume offer different theoretical perspectives on the nature of engagement, interaction and immersion in threshold spaces, and the factors which enable and inhibit those immersive possibilities. Organised into themed sections, the book explores museum thresholds from three different perspectives. Considering them first as a problem space, the contributors then go on to explore thresholds through different media and, finally, draw upon other subjects and professions, including performance, gaming, retail and discourse studies, in order to examine them from an entirely new perspective. Drawing upon examples that span Asia, North America and Europe, the authors set the entrance space in its historical, social and architectural contexts. Together, the essays show how the challenges posed by the threshold can be rethought and reimagined from a variety of perspectives, each of which have much to bring to future thinking and design.Combining both theory and practice, Museum Thresholds should be essential reading for academics, researchers and postgraduate students working in museum studies, digital heritage, architecture, design studies, retail studies and media studies. It will also be of great interest to museum practitioners working in a wide variety of institutions around the globe."--Provided by publisher.